2017
DOI: 10.1007/s11920-017-0797-3
|View full text |Cite
|
Sign up to set email alerts
|

Eating Disorders and the Intestinal Microbiota: Mechanisms of Energy Homeostasis and Behavioral Influence

Abstract: Purpose of review We reviewed and evaluated recently published scientific studies that explored the role of the intestinal microbiota in eating disorders. Recent findings Studies have demonstrated that the intestinal microbiota is a contributing factor to both host energy homeostasis and behavior—two traits commonly disrupted in patients with eating disorders. To date, intestinal microbiota research in eating disorders has focused solely on anorexia nervosa (AN). Initial studies have reported an atypical int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
44
0
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 53 publications
(48 citation statements)
references
References 82 publications
1
44
0
3
Order By: Relevance
“…Furthermore, physical anxiety can include interoceptive experiences involving gastrointestinal distress, which can impact feelings of hunger and fullness. Recent reviews of the relationship between gastrointestinal symptoms and eating disorders highlight the potential for complex and reciprocal relationships between eating disorder, anxiety, and gastrointestinal symptoms (Conviser, Fisher, & McColley, ; Norris et al., ), which may be mediated by variations in gut microbiota (Glenny, Bulik‐Sullivan, Tang, Bulik, & Carroll, ; Kleiman et al., ).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, physical anxiety can include interoceptive experiences involving gastrointestinal distress, which can impact feelings of hunger and fullness. Recent reviews of the relationship between gastrointestinal symptoms and eating disorders highlight the potential for complex and reciprocal relationships between eating disorder, anxiety, and gastrointestinal symptoms (Conviser, Fisher, & McColley, ; Norris et al., ), which may be mediated by variations in gut microbiota (Glenny, Bulik‐Sullivan, Tang, Bulik, & Carroll, ; Kleiman et al., ).…”
Section: Discussionmentioning
confidence: 99%
“…Recently, the prospective role of Fecal Microbiota Transplant (FMT) was evaluated in the management of ED. To date, only promising preclinical studies about the positive effects of microbiota restoration on mood disorders are available [140][141][142]; for this reason, future studies should focus on the possibility of translating these results in human studies.…”
Section: Gut Microbiotamentioning
confidence: 99%
“…Heterogeneity: I 2 = 87%, τ 2 = 703.4575, p < 0.01 Barja−Fernandez et al 2015Boland et al 2001Curatola et al 2004Delporte et al 2003Franssila−Kallunki et al 1991Heilbronn et al 2007Karczewska−Kupczewska et al 2010Kaválková et al 2012Krízová et al 2008Lejoyeux et al 1996Matzkin et al (all) 2006Matzkin et al (all) 2007Misra et al 2006Mordasini et al 1977Nestel et al 1974Nova et al 2008Omodei et al 2015Rigaud et al 2009 191.4 199.0 167.6 186.0 189.5 205.0 162.4 174.6 295.4 185.6 282.3 191.4 191.3 144.7 265.0 318.8 208.2 171.7 190.0 199.5 204.2 184.8 162.6 197.8 201.1 189.5 192 Furthermore, some studies suggest increased absorption of exogenous cholesterol indicated by higher concentrations of the phytosterol campesterol and beta-sitosterol-steroids derived from plantsin individuals with AN (Zák et al, 2003;Zák et al, 2005), and potentially, these changes in absorption may be influenced by alterations in gut microbiota (Glenny, Bulik-Sullivan, Tang, Bulik, & Carroll, 2017;Schwensen, Kan, Treasure, Hoiby, & Sjogren, 2018). Increased endogenous cholesterol synthesis seems to be unlikely in individuals suffering from AN (Feillet et al, 2000;Weinbrenner et al, 2004;Zák et al, 2003;Zák et al, 2005).…”
Section: Random Effects Modelmentioning
confidence: 99%